2020
DOI: 10.3389/fmars.2020.00497
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the Skill of Coupled Physical–Biogeochemical Models in the NW Mediterranean

Abstract: Numerical modeling is a key tool to complement the current physical and biogeochemical observational datasets. It is essential for understanding the role of oceanographic processes on marine food webs and producing climate change projections of variables affecting key ecosystem functions. In this work, we evaluate the horizontal and vertical patterns of four state-of-the-art coupled physical-biogeochemical models, three of them already published. Two of the models include data assimilation, physical and/or bio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 84 publications
(109 reference statements)
0
7
0
Order By: Relevance
“…These considerations emphasize the importance of providing eddy-resolving future projections of the Mediterranean Sea biogeochemistry under different emission scenarios. In fact, although observational and modeling studies have been already carried out in the recent period to assess the importance of the mesoscale dynamics for the physical and biogeochemical states of limited areas of the Mediterranean Sea (e.g., Hermann et al, 2008;Moutin and Prieur, 2012;Guyennon et al, 2015;Ramirez-Romero et al, 2020), long-term eddy-resolving biogeochemical projections under different emission scenarios have not yet, to the best of the authors' knowledge, been analyzed for this region. Such projections might be used in future studies specifically focused on the analysis of climate change impacts on specific organisms, habitats and/or local areas.…”
Section: Introductionmentioning
confidence: 99%
“…These considerations emphasize the importance of providing eddy-resolving future projections of the Mediterranean Sea biogeochemistry under different emission scenarios. In fact, although observational and modeling studies have been already carried out in the recent period to assess the importance of the mesoscale dynamics for the physical and biogeochemical states of limited areas of the Mediterranean Sea (e.g., Hermann et al, 2008;Moutin and Prieur, 2012;Guyennon et al, 2015;Ramirez-Romero et al, 2020), long-term eddy-resolving biogeochemical projections under different emission scenarios have not yet, to the best of the authors' knowledge, been analyzed for this region. Such projections might be used in future studies specifically focused on the analysis of climate change impacts on specific organisms, habitats and/or local areas.…”
Section: Introductionmentioning
confidence: 99%
“…In the NW Mediterranean, primary production is determined by the strong vertical mixing and contribution of fluvial nutrient loads [24]. Considerable differences in seawater temperature are reported in this area [25]. Therefore, due to its environmental heterogeneity and particular hydrographical feature, it is of primary interest to study the life history traits of sardine in this area, as well as its parasite infection.…”
Section: Introductionmentioning
confidence: 99%
“…PISCES has been used and validated in a number of settings (Ramirez-romero et al, 2020;Gutknecht et al, 2019;Kwiatkowski et al, 2018). Skyllas et al (2019) showed a good agreement between EC-Earth3-CC and temperature, salinity, and nutrients and chlorophyll a observations in an offline ocean-only version of NEMO-PISCES, for a northsouth (29-63°N) transect in the northwest Atlantic.…”
Section: Ec-earth3-ccmentioning
confidence: 95%